Oral Manifestations Associated with COVID-19 Infection: A Cross-Sectional Study of Recovered Iraqi Patients - Mohanad Jameel Najm Al-Magsoosi; Oras Kadhim Baqer Al-Asadi; Nibrass Talib Al-Quraine; Suha Mohammad Sami; Julfikar Haider (International Journal of Dentistry)
Aims. The aim of this study was to determine prevalence of oral manifestations related to COVID-19 infection among a sample of recovered patients in the Basrah province of Iraq. Methodology. This cross-sectional study included a total of 574 individuals from Basrah city, Iraq (196 males and 378 females), who had been previously infected with COVID-19. A questionnaire was developed and used to record the demographic data, medical history, severity of respiratory infection followed by hospitalization along with oral signs and symptoms that occurred during the COVID-19 infection and their persistence after recovery. Results. Oral manifestations were reported in 88.3% of the studied sample. The most common oral manifestation was ageusia (66.8%), followed by dry mouth (59%), gustatory changes (46%), dysphagia (40.5%), burning sensation (20.8%), oral ulceration (14.5%), and gingival bleeding (3.3%). The findings suggested that ageusia was the only symptom that persisted following recovery from the COVID-19 infection. The results showed a significant statistical correlation between the incidence of oral manifestations and the severity of COVID-19 infection followed by hospitalization. A significant correlation was also found between the age groups and COVID-19 oral manifestations, whereas no significant statistical relationship was observed between gender, smoking, and systemic diseases. Conclusions. COVID-19 infection has considerable impacts on the oral cavity and salivary glands and after recovery from the infection, some patients continue to complain of ageusia for several months. There is a positive correlation between the incidence of oral signs and symptoms associated with COVID-19 infection and the severity of the infection.